Standardization and Diffusion of Shariah Principles in Hospitality: A Study of Shariah-Compliant Hotels in Malaysia’s Halal Tourism Sector - Amir, Ahmad Nabil; Rahman, Tasnim Abdul (Al-Risalah, 2025)
This study investigates the operational frameworks, regulatory challenges, and economic impacts of Shariah-Compliant Hotels (SCHs) in Malaysia, aiming to evaluate their role in advancing Islamic tourism and strengthening Malaysia’s position as a global leader in halal hospitality. Employing a mixed-method approach, the research integrates qualitative narrative analysis with quantitative data, including semi-structured interviews with 12 managers from MFAR-recognized hotels and a review of secondary sources such as government reports and certification guidelines. The Diffusion of Innovation (DOI) framework is used to assess how SCHs adopt and implement Islamic hospitality standards. The findings reveal that Malaysian SCHs successfully embed Islamic values in service delivery, offering halal-certified food, gender-segregated facilities, prayer spaces, and Shariah-aligned amenities. However, challenges remain—particularly fragmented certification systems between JAKIM and the Islamic Tourism Centre, lack of staff training, and unclear compliance standards. Despite these barriers, the sector contributes significantly to tourism growth, as evidenced by 5.33 million Muslim tourist arrivals in 2019, and attracts foreign direct investment, especially from Gulf Cooperation Council (GCC) countries. This study offers a more holistic understanding of SCHs by bridging theoretical perspectives and empirical findings. It recommends improved standardization, cross-agency coordination, and policy innovation to sustain Malaysia’s leadership in halal tourism and expand into areas such as Islamic fintech, halal medical tourism, and value-driven investment models.